Implementasi Open Source Enterprise Resource Planning Menggunakan Odoo Pada Layanan Internet Desa - Jacky Ma'ruf Fatoni; Aryo Nugroho (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
The development of information technology in the era of industrial revolution 4.0 has created competition between business companies. Information technology that always develops can be a solution for companies to keep innovating in order to build their business. One of the parts in the industrial world that always grows is a company which engages in digital infrastructure. There is one company that provides internet network services, data centers, and cloud computing which has the desire to be able to optimize its business activities in helping to equalize the area so that it is affordable by several internet network service providers which it can balance with the application of information technology in accordance with the company's business processes, so that information system technology is used that can integrate all line of business entities in real-time, namely Enterprise Resource Planning (ERP). Therefore, it takes automation and integration of business processes using an ERP system. The ERP system that will be applied in this research uses open source-based software, namely Odoo, with 10.0 version because it can adapt to the company's needs. The results of black-box testing on the implementation of business processes run as expected.